The Consumption of Popular Pop Culture in Japanese Language Culture Learning at the University - Permatasari, Kun Makhsusy; Thamrin, Muhammad; Robihim (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Popular Japanese pop culture is widely loved by students in Indonesia. This study aims to examine the use of popular pop culture by students while studying the Japanese language and culture. This study uses a qualitative research design with a qualitative descriptive method. The study was conducted at the Japanese Language and Culture Study Program at Darma Persada University, Jakarta, in the odd academic year 2024/2025 from September to December 2024. The subjects of the study were 100 people, consisting of 50 men and 50 women. The data collection techniques used were interviews, observations and forum group discussions. Data analysis techniques have three steps: data reduction, data presentation, and inference drawing and verification. The study’s findings revealed that popular pop culture that is widely loved by students to learn Japanese culture and language is anime/cartoons and manga/comics. The background knowledge of students about Japanese popular culture has a significant influence on the choice of types of Japanese pop culture and can be used as authentic material in class. Popular language pop culture has an important role in the concept of building a learning environment that is under the character of the language culture. The results of the study can recommend to lecturers to research the development of authentic teaching materials from various types of popular Japanese pop culture.